Stability Indicating RP-HPLC Method Development for Drotaverine Hydrochloride Using PDA Detection - P. Dahivelkar, Prasad; Bari, S.B. (Asian Journal of Chemistry, 2011)
A sensitive, selective, precise and stability-indicating HPLC method for analysis of drotaverine hydrochloride both as bulk drug and in formulation was developed and validated. The drug was subjected to acid, base hydrolysis (0.1 M HCl and 0.1 M NaOH) and oxidative decomposition (2.5 % v/v H2O2). The study was carried out from room temperature to 60 ºC and observed for 10 % decomposition. The degradation products were separated on a C8 (phenomenax, 250 mm × 4.6 mm) chromatographic column with mobile phase comprising of methanol: 0.05 M KH2PO4 (pH 3.5, 55:45 v/v) pumped at 1 mL/min. The drug was estimated at 241 nm. Retention time of drotaverine hydrochloride was 8.705 min, whereas retention time of base degradation products were 3.696, 4.001 and 6.532 min. The drug was relatively stable to acidic and oxidative degradation conditions, where the degradation occurred in a tune of 10-15 %. The method was validated in accordance with ICH guidelines. The developed method is stability indicating and can be used in drug development and testing laboratory for the quality control.